Relationships of entanglement: an interrogation into the historical, economic and political factors that shape political interactions in Zimbabwe - Nyaku, Faithful (Department of Political Studies, 2026)
This thesis explores the complex dynamics that define Zimbabwe's political landscape, particularly the interactions between political actors during elections. It investigates how historical, economic, political, and international pressures shape these relationships and influence the conduct of elections, shedding light on how these factors perpetuate contentious political behaviours such as election rigging, censorship, voter intimidation, violent repression, and the weaponisation of the law. By situating these empirical observations within a scholarly framework, the thesis seeks to deepen the intellectual understanding of Zimbabwe's volatile political ecosystem. At the core of the study is an examination of how elections serve as both a source of opportunity and threat within Zimbabwe's political sphere. On one hand, they offer the potential for regime change, particularly for opposition movements like the CCC, while on the other, they represent a challenge to the long-established dominance of ZANU-PF. The lingering memory of previous elections marred by violence, abductions, and predictable outcomes exacerbates this tension. The complicity of observer groups, the strategic weaknesses of the opposition, and the drive for political parity further entangle these relationships. The thesis traces the roots of these dynamics back to Zimbabwe's colonial history, revealing how colonial and post-colonial legacies continue to shape political interactions today. These historical pressures, coupled with contemporary global forces advocating for democratisation and good governance, influence the behaviour of political actors. The international community plays a dual role as both enabler and watchdog, facilitating political processes while also monitoring electoral violence and coercion. Furthermore, the research delves into how elections are used as a means for political actors to assert their identity and redefine notions of citizenship. Drawing on theories of identity and citizenship, the thesis argues that the tensions surrounding elections are not only about political power but also about who belongs in the nation-state. The ruling party's use of electoral authoritarianism is seen as a way to define citizenship, creating exclusionary narratives about identity and belonging in Zimbabwe's political and social fabric. Through this lens, the thesis presents elections as pivotal moments that reveal deeper struggles over identity, power, and national membership.